Validation and Psychometric Properties of the Minnesota Living With Heart Failure Questionnaire in Individuals With Coronary Artery Disease in Lithuania - Gecaite-Stonciene, Julija; Burkauskas, Julius; Bunevicius, Adomas; Steibliene, Vesta; Macijauskiene, Jurate; Brozaitiene, Julija; Mickuviene, Narseta; Kazukauskiene, Nijole (Frontiers in Psychology, 2022)
Background. Health related quality of life (HRQoL) is known to be impaired in individuals with coronary artery disease (CAD), especially in those after a recent acute coronary syndrome (ACS). Heart failure a common burden in this population that significantly contribute to worsen HRQoL. To accurately measure the level of HRQoL in individuals with CAD after ACS, disease specific scales, such as The Minnesota Living with Heart Failure Questionnaire (MLHFQ), are recommended. Nevertheless, to date, there has not been study that would comprehensively evaluate psychometric properties of the MLHFQ in a large sample of individuals with CAD after ACS. The debate regarding internal structure of MLHFQ is also still present. Hence, this study aimed to translate the MLHFQ and evaluate its internal structure, reliability/precision and validity in individuals with CAD following ACS in Lithuania. Methods. In the cross-sectional study, 1083 participants (70% men, age M=58, SD=9) were evaluated for socio-demographic and clinical characteristics. HRQoL was measured using the MLHFQ and the Short Form-36 health survey (SF-36). In addition, exercise capacity (EC) was also evaluated in the study patients, using a standardized computer-driven bicycle ergometer. Results. The internal consistency of the MLHFQ subscales (.79-.88) were found to be good. Confirmatory factor analysis provided the support for the three-factor model (“physical domain”, “social domain”, and “emotional domain”) of the MLHFQ and showed acceptable fit (CFI = .894; GFI = .898; NFI = .879, RMSEA = .073). Regarding convergent evidence, significant associations were found between the MLHFQ domains and the SF-36 domains as well as EC (r’s range .11-.58). Conclusions. The current study completed cultural validation and provided further information on the psychometric characteristics of the MLHFQ in Lithuania, suggesting MLHFQ as valid and reliable instrument to measure HRQoL. The Lithuanian version of MLHFQ is best described by three-factor solution, measuring physical, social and emotional dimensions of HRQoL among individuals with CAD following ACS.